Conflict resolution methods among a sample of secondary school teachers in the city of Jableh (Journal of Hama University, 2026)
The current research aims to identify the most common conflict resolution methods among a sample of secondary school teachers in the city of Jableh, in addition to identifying the differences in the use of conflict resolution methods according to the variable of gender and number of years of experience. The researcher relied on the Thomas and Kilman model in addition to a number of previous studies in preparing the questionnaire, and it was applied to a sample of 100 male and female teachers in Jableh secondary schools after studying the psychometric properties and ensuring its validity for application. The results showed that the most common conflict resolution methods among the sample members are the cooperation method, followed by the settlement method, then withdrawal, absorption, and finally competition. The results also showed that there is no statistically significant difference in the use of the five methods according to the gender variable, and there are statistically significant differences in the use of the methods (cooperation - settlement - competition - withdrawal) according to the variable of the number of years of experience in favor of teachers with more than 10 years of experience, and there are no differences according to this variable in the use of the absorption method.
Keywords: Conflict resolution methods; secondary school teachers